Factors Affecting Foreign Investment to Invest in Lao PDR Case Study: Chinese Investors in Chengdu of China: https://doi.org/10.69692/SUJMRD0802260 - HOONGSENGPHA, Soudthida; SAYJALERN, Paengphimpha; PHOMMACHACK , Thongkhoun; CHANTHALASY , Dokkeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research on the factors affecting foreign investment in Lao PDR emphasized the input factors which include 7 mains aspects: government policy, economic, socio-cultural, infrastructure, market-competition, natural resources and Labor-skills. The key sample participants of this investigation were Chinese entrepreneurs-businessmen who are operating business in Chengdu, Sichuan of China with the number of 196. The tool used for data collection was the questionnaire and the statistical software (SPSS) was employed for Binary Logistic Regression Analysis for testing and forecasting. The results of the study revealed that the factors used in the research have a positive relationship with the factors that affect foreign investment in the Lao PDR. With a statistical significance level of 0.05 above which include: 1) Economic Factors, 2) Infrastructure Factors, and 3) Natural Resource Factors with a statistical significance level of 0.05.